Is Vaccination Related to The Cure Rate of COVID-19 Patients with Comorbidities? - Mia Herdiyani Achmad; Reviono Reviono; Yusup Subagio Sutanto; Jatu Aphridasari; Windu Prasetyo (Jurnal Respirologi Indonesia, 2023)
Background: Prior vaccination can prevent a COVID-19 patient from falling into moderate, severe, and critical conditions. The effect of vaccination on COVID-19 patients’ recovery has been widely studied. However, its correlation in critically severe COVID-19 patients with comorbidity has not been fully understood yet. This study aims to determine the correlation of vaccination in critically severe COVID-19 patients with comorbidity of hypertension and/or Diabetes Mellitus (DM).Methods: A retrospective cohort study was conducted in critically severe COVID-19 patients with hypertension and/or DM treated in Dr. Moewardi Hospital, Surakarta, Indonesia from March 2021 to September 2021. The data were taken from patients’ medical records. We analyzed all data statistically with Chi-Square and fisher's exact test, and a p-value of < 0.05 was considered significant.Results: There were 489 patients included in our study, 247 patients with hypertension and DM, and 242 patients without comorbidities. Vaccination status was significantly associated with the cure rate of critically severe COVID- 19 patients with hypertension (p=0.018), but not with DM (p=0.606). There was no significant association between age to the cure rate of critically severe COVID-19 patients with hypertension and DM (p=0.953). Vaccination status was related among patients with comorbidities and without comorbidities (p<0.001).Conclusion: Vaccination was significantly correlated the cure rate of moderate to critically severe COVID-19 patients with hypertension and without comorbidities.